Histone H3.3 incorporation provides a unique and functionally essential telomeric chromatin in embryonic stem cells - Wong, Lee H.; Ren, Hua; Williams, Evan; McGhie, James; Ahn, Soyeon; Sim, Marcus; Tam, Angela; Earle, Elizabeth; Anderson, Melissa A.; Mann, Jeffrey; Choo, K.H. Andy

(untitled) (Genome Research, 2009)
Little is known about the telomere chromatin dynamics of embryonic stem (ES) cell. Here, we demonstrate localization of histone H3.3 at interphase telomeres and enrichment of Ser31-phosphorylated H3.3 at metaphase telomeres in pluripotent mouse ES cells. Upon differentiation, telomeric H3.3S31P signal decreases, accompanied by increased association of heterochromatin repressive marks and decreased micrococcal nuclease sensitivity at the telomeres. H3.3 is recruited to the telomeres at late S/G2 phase, coinciding with telomere replication and processing. RNAi-depletion of H3.3 induces telomere-dysfunction phenotype, providing evidence for a role of H3.3 in the regulation of telomere chromatin integrity in ES cells. The distinctive changes in H3.3 distribution suggests the existence of a unique and functionally essential telomere chromatin in ES cells that undergoes dynamic differentiation-dependent remodeling during the process of differentiation.